Australian Garden Centre Accreditation Scheme (AGCAS) manual - Nursery & Garden Industry Australia (Sydney : Nursery & Garden Industry Australia, 2007)
"The Australian Garden Centre Accreditation Scheme (AGCAS) is a national, industry managed scheme designed to raise the overall standards of garden centre retailing in Australia. The scheme addresses four main areas of garden centre operations: the quality of the product on offer; the experience and knowledge of the staff and their ability to provide inspirational advice; the quality of the centre's premises; the scope and nature of the garden centre's promotional activities."--Introduction to AGCAS.
Updated in 2007. Previously published in 2000 and 2004.
Includes bibliographical references.
Keywords: Australian Garden Centre Accreditation Scheme; Nurseries (Horticulture) -- Australia -- Accreditation; Garden centers (Retail trade) -- Australia -- Accreditation; Plant growing media -- Australia